Genetic connectivity of the coral‐eating sea star A canthaster planci during the severe outbreak of 2006–2009 in the S ociety I slands, F rench P olynesia - Nina Yasuda; Coralie Taquet; Satoshi Nagai; Terutoyo Yoshida; Mehdi Adjeroud (Marine Ecology, 2015)
Occasional population outbreaks of the crown‐of‐thorns sea star, A canthaster planci , are a major threat to coral reefs across the Indo‐Pacific. The presumed association between the serial nature of these outbreaks and the long larval dispersal phase makes it important to estimate larval dispersal; many studies have examined the population genetic structure of A . planci for this purpose using different genetic markers. However, only a few have focused on reef‐scale as well as archipelago‐scale genetic structure and none has used a combination of different genetic markers with different effective population sizes. In our study, we used both mt DNA and microsatellite loci to examine A . planci population genetic structure at multiple spatial scales (from DNA (global F ST = −0.007, P = 0.997) and low levels of genetic structure using microsatellite loci (global F ST = 0.006, P = 0.005). We found no significant isolation by distance patterns within the study area for either genetic marker. The overall genetically homogenized pattern found in both the mitochondrial and nuclear loci of A . planci in the Society Archipelago underscores the significant role of larval dispersal that may cause secondary outbreaks, as well as possible recent colonization in this area.